Prenatally diagnosed microdeletion in the TCOF1 gene in fetal congenital primary Treacher Collins Syndrome - Wei Shin Chou; Jia Shing Chen; Yu Ming Shiao; Ju Chin Tsauer; Yi Fen Chang; Ching Hua Hsiao (Elsevier, 2022)
Objective: To study prenatal diagnosis of congenital Treacher Collins syndrome, an etiology of craniofacial abnormalities. Case report: We present a case of fetal craniofacial abnormalities identified by antepartum sonography screening in the third trimester (28 weeks); features of micrognathia, hypoplastic zygomatic arches and bilateral low-set microtia were detected. Due to the unknown severity of the craniofacial abnormalities and poor prognosis, the parents decided to terminate the fetus after through counselling. A normal female karyotype was detected. The parents consented to chromosome microarray analysis (CMA), which identified a de novo mutation of the TCS1 gene locus on chromosome 5. Conclusion: Molecular CMA is an effective tool for prenatal diagnosis of congenital craniofacial abnormalities associated with Treacher Collins syndrome.